2022
DOI: 10.4049/jimmunol.2100577
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant HO-1/NQO1–Reactive Oxygen Species–ERK Signaling Pathway Contributes to Aggravation of TPA-Induced Irritant Contact Dermatitis in Nrf2-Deficient Mice

Abstract: NF-erythroid 2–related factor 2 (Nrf2) is a major transcription factor to protect cells against reactive oxygen species (ROS) and reactive toxicants. Meanwhile, Nrf2 can inhibit contact dermatitis through redox-dependent and -independent pathways. However, the underlying mechanisms of how Nrf2 mediates irritant contact dermatitis (ICD) are still unclear. In this article, we elucidated the role of Nrf2 in 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced acute ICD. Our study demonstrated that the ear thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The nuclear erythroid 2-related factor 2 (NERF2) is a transcription factor with anti-inflammatory, antioxidant properties which is involved in enzyme biosynthesis and biotransformation of lipids and carbohydrates (Besednova et al, 2022). Nrf2 plays a key role in maintaining homeostasis; therefore, protect organs especially cardiopulmonary, renal, and nervous systems against cancer and other disorders caused by increased oxidative stress (Gall Trošelj et al, 2022;Huang et al, 2022;Hybertson, Gao, & McCord, 2022;Wang, Long, Lin, Wang, & Wang, 2022;Zhu et al, 2022). Thus, the potential interaction of resveratrol with the Nrf2 pathway in preventing obesity, diabetes, and cancer should be taken into consideration (Kay et al, 2015;Das & Banik, 2022;Lynn, Park, Ogunwale, & Acquaah-Mensah, 2022;Malaguarnera et al, 2018;Meng, Zhou, Zhao, Gan, & Li, 2020;Nakata, Takahashi, & Inoue, 2012;Piotrowska, Kucinska, & Murias, 2012;Shahidi & Ambigaipalan, 2015;Talebi, Talebi, Farkhondeh, & Samarghandian, 2022;Thiel & Rössler, 2017;Wen, Zhang, Yang, Elias, & Man, 2020).…”
mentioning
confidence: 99%
“…The nuclear erythroid 2-related factor 2 (NERF2) is a transcription factor with anti-inflammatory, antioxidant properties which is involved in enzyme biosynthesis and biotransformation of lipids and carbohydrates (Besednova et al, 2022). Nrf2 plays a key role in maintaining homeostasis; therefore, protect organs especially cardiopulmonary, renal, and nervous systems against cancer and other disorders caused by increased oxidative stress (Gall Trošelj et al, 2022;Huang et al, 2022;Hybertson, Gao, & McCord, 2022;Wang, Long, Lin, Wang, & Wang, 2022;Zhu et al, 2022). Thus, the potential interaction of resveratrol with the Nrf2 pathway in preventing obesity, diabetes, and cancer should be taken into consideration (Kay et al, 2015;Das & Banik, 2022;Lynn, Park, Ogunwale, & Acquaah-Mensah, 2022;Malaguarnera et al, 2018;Meng, Zhou, Zhao, Gan, & Li, 2020;Nakata, Takahashi, & Inoue, 2012;Piotrowska, Kucinska, & Murias, 2012;Shahidi & Ambigaipalan, 2015;Talebi, Talebi, Farkhondeh, & Samarghandian, 2022;Thiel & Rössler, 2017;Wen, Zhang, Yang, Elias, & Man, 2020).…”
mentioning
confidence: 99%
“…Mounting evidence suggests that the identification of possible biomarkers and targets is critical for the effective treatment of cutaneous inflammatory disorders. 32,33 Our study is the first to identify ADAM23 as a potential biomarker for psoriasis. Our results show that ADAM23 may be upregulated in macrophage-rich psoriatic lesions in psoriatic mice as well as in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous studies showed that nuclear factor E2-related factor 2 (NRF2), a master switch that induces antioxidant enzymes, is required for the anti-inflammatory effects of AHR activation in human keratinocytes ( 26 , 27 ). Since the dysfunction of NRF2 has been reported to potentiate skin inflammation ( 28 ), activators of the AHR-NRF2 axis should be candidate therapeutic agents for inflammatory skin diseases such as AD and psoriasis ( 14 ). Specifically, tapinarof is a potential new topical treatment for AD and psoriasis as a therapeutic AHR-modulating agent ( 29 ).…”
Section: Discussionmentioning
confidence: 99%